Pengaruh Terapi Progressive Muscle Relaxation (PMR) terhadap Depresi Pada Lansia di Panti Sosial Tresna Werdha (PSTW) Sabai Nan Aluih Sicincin - Rezky Pradessetia; Rika Sabri; Dewi Eka Putri (Universitas Batanghari Jambi, 2021)
The problem of depression is still common in Indonesia. West Sumatra is in seventh position out of 34 provinces with the most depression problems. There are four treatments for depression in the elderly, namely psychological, medical, spiritual and physical approaches. Progressive Muscle Relaxation (PMR) therapy makes the body relax. feeling calm so tension is reduced. With a feeling of relaxation and calm, individuals will find it easier to feel calm in their thoughts and feelings. Aim Knowing the effect of Progressive Muscle Relaxation (PMR) therapy on depression in the elderly. Experimental research with Quasi experimental design pre and post test with control group. The sampling technique is simple random sampling. The sample consisted of 40 elderly people, who were divided into two groups, namely the intervention group and the control group. Measurement of depression scores using the Geriatric Depression Scale (GDS) questionnaire with a total of 15 questions. Data analysis using Paired Sample T Test test. There was a decrease in depression scores after being treated with Progressive Muscle Relaxation (PMR) therapy in the intervention group, with p = 0.000 (p <0.05). This shows that there is a change in depression scores experienced by the elderly after being given Progressive Muscle Relaxation (PMR) Therapy. Therapy Progressive Muscle Relaxation (PMR) can be applied as a non-pharmacological therapy at the Panti Tresna Werdha (PSTW).